(untitled) (Collection of scientific works «Modern structures of metal and wood», 2021)
Due to the simplicity of design and manufacture, as well as reliability during operation, beams are one of the most common elements used in industrial, civil and public construction. The most rational cross-section of metal beams are rolled I-beams with inclined or parallel inner faces of the shelves, the predominant use of which is due to the value of the core distance, which is twice as much the same value for a rectangular section and almost three times for a round section. This figure is even higher for perforated profiles obtained from conventional rolling beams, which allow you to compose sections with increased values of moments of inertia and moments of resistance without increasing material consumptions. For inseparable beams, an additional significant factor influencing on their bearing capacity, is the structural design of the intermediate support part. The aim of these researches is to study the stress-strain state of inseparable perforated beams of I-beam profile of different heights in areas near the intermediate support, the design of which is made without a transverse stiffening rib placed on the axis of the support, and with unwelded holes to the left and right of the support under the action of evenly distributed load in the software complex "Lira". The objectives of the study are to establish the actual values of stresses and strains in the characteristic cross sections of the inseparable perforated I-beam, which occur on the intermediate support, and perform a comparative analysis of numerical studies obtained in the software complex "Lira" for intermediate support node beams of different heights for actions of different magnitudes of loads. The analysis of the obtained diagrams of normal stresses was carried out, which showed that for the proposed design of the support part of the beam, the cross-sections with holes directly to the left and right of the support are calculated. The conclusion about necessity of carrying out further experimental-theoretical researches of various types of support parts of beams for the purpose of development of a complex technique of their calculation and recommendations on definition of rational scope of application of each of them is formulated.